1983
DOI: 10.1007/bf02332944
|View full text |Cite
|
Sign up to set email alerts
|

Valepotriate content in different in vitro cultures of Valerianaceae and characterization of Valeriana officinalis L. callus during a growth period

Abstract: Different in vitro cultures of Valerianaceae were analysed for valepotriate content [(iso)valtrate, acevaltrate, didrovaltrate] in a study on properties of production in vitro (plant species, growth conditions, differentiation level, valepotriate content of the medium after growth). The in vitro cultures were: callus cultures of Valeriana officinalis L., Valerianella locusta L. and Centranthus ruber L.DC.; a suspension culture of Valeriana officinalis L. and a root organ culture of Centranthus ruber L.DC. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…The valepotriate content of different Valerianaceae tissue cultures was studied [21,22,122,159,160,161]. The yield of valepotriates and the relative amounts of the components varied from species to species.…”
Section: Valepotriates -Dicotyledonsmentioning
confidence: 99%
See 3 more Smart Citations
“…The valepotriate content of different Valerianaceae tissue cultures was studied [21,22,122,159,160,161]. The yield of valepotriates and the relative amounts of the components varied from species to species.…”
Section: Valepotriates -Dicotyledonsmentioning
confidence: 99%
“…Since no valepotriates were detected in the culture media, it was concluded that these compounds were accumulated intracellularly [159]. The influence of artificially-induced higher ploidy levels on the valepotriate production by suspension cultures of Valeriana wallichii DC.…”
Section: Valepotriates -Dicotyledonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the essential oil of valerian depends on the chemovar, and the most common compounds include bornyl acetate, valerenal, valeranone, and cryptofauronol. 19 Minor constituents of the essential oil include α -pinene, β -pinene, camphene, β -caryophyllene, terpinolene, limonene, and carvyl acetate.…”
Section: Chemical Compositionmentioning
confidence: 99%